From Colonies to Countries in the North Caribbean : Military Engineers in the Development of Cities and Territories - Luengo Gutiérrez, Pedro (Cambridge Scholars Publishing, 2016)
This volume brings together eight essays that address the result of a research project involving a group of international scholars. It explores a little-discussed, yet interesting phenomenon in the Caribbean and Gulf of Mexico region - how military engineers reshaped the physical landscape for imperial reasons and, in doing so, laid the foundations for broader colonial development. Moreover, this transnational scenario reveals how military construction reached beyond cross-borders themes and histories from the age of imperialism. As such, this book provides valuable insights into the role of m.